Integrated Identification and Efficient Use of Biodiversity in Mountainous Regions - Mehdiyeva A. M.; Mahmudova Z. A.; Rustamova D. F.; Mansurova D.; Juraeva G. (BIO Web of Conferences)
The article studies the comprehensive identification and efficient use of biodiversity (geothermal sources) in mountainous regions. Discussion of the ways to solve the most acute problems affecting mountainous regions with complex relief has always been on the agenda as a topical issue. The purpose of the presented work is to determine the quantitative, qualitative and thermodynamic parameters of geothermal sources in these territories, as well as the spatial structure of the foci of formation of their migration routes. Conducting a comprehensive assessment of the biodiversity of deforested mountainous regions substantiates the need to ensure the protection of these unique ecosystems. The issue of determining the direction of the integrated use of geothermal resources is studied not only by its structure and characteristics, but also by the level of development of complex technological processes for the extraction and processing of hydromineral raw materials and the technology of thermal energy processes. Using a number of analytical research methods (hydrogeological, geochemical, geophysical, isotope, computer (mathematical) modeling and others) to solve these problems, we determine the foci of formation of reservoir conditions in individual horizons, migration routes, as well as quantitative and qualitative parameters of thermal waters. The following issues were studied: hydrogeological research methods will help to identify the development zone of the intensive circulation aquifer (active water exchange) and the base of the development zone of the deep underground flow aquifer (impeded exchange) in the underground hydrosphere zones, and to assess their hydrodynamic and hydrothermal conditions and parameters. Based on the data from drilled exploratory oil wells, the conditions for the formation of thermal water layers in various hydrogeological structures will be determined; hydrochemical research methods will be aimed at assessing the macro- and microcomponent composition and radiation background of thermal waters at various intervals of migration routes by determining various indicators at different depths of their formation (based on the petrochemical structure of the geological part); isotopic studies of the gas composition of thermal waters will help to identify their genesis and use them as a marker when determining the points of formation; computer modeling of the underground hydrosphere of a representative object was carried out using mathematical programs.